THE RELATIONSHIP BETWEEN THE HEAD OF MADRASAH AND THE LEADERSHIPTEACHER PERFORMANCE ON STUDENT CHARACTER EDUCATION - Kurniawati, Desi; Abdul Adib; Widiastuti, Nur (UNISAN JURNAL, 2023)
The head of the madrasa as a leader in the education unit plays a role and is responsible for organizing, monitoring, fostering and improving the teaching and learning process in the classroom. This study aims to: (1) find out how big the relationship between the leadership style of the madrasa principal on the characteristics of the students of SDN 63 Gedong tataan Pesawaran, (2) find out how much influence the teacher's performance has on the character education of students at SDN 63 Gedong tataan Pesawaran, (3) find out how much the relationship between the principal's leadership style and teacher performance on student character education at SDN 63 Gedong tataan Pesawaran. The research used in this study was quantitative. Collecting data in this study using a questionnaire consisting of the leadership style of the madrasa principal, teacher performance, and student learning achievement. The number of respondents in this study were 40 teachers and 40 students. The results of data analysis show that: (1) there is a relationship between the leadership style of the madrasa principal on the education of students' characteristics which is explained by the results of the significant value of the t-test which has a magnitude of 0.002 with a percentage of 67.5%, (2) there is an effect of teacher performance on learning achievement. students described by the results of the significant value of the t-test which has a magnitude of 0.001 with a percentage of 69.9%, (3) there is a relationship between the leadership style of the madrasa principal and teacher performance on the character of the students with a significant value of 0.002. the magnitude of the relationship between the leadership style of the madrasa principal on teacher performance and student character is 70.3%